Compact Silicon Waveguide Mode Converter Employing Dielectric Metasurface Structure. Issue 4 (14th December 2018) - Wang, Hongwei; Zhang, Yong; He, Yu; Zhu, Qingming; Sun, Lu; Su, Yikai
Abstract: Mode converters are key components in on‐chip mode‐division multiplexing systems. A compact silicon waveguide mode converter is proposed and demonstrated using all‐dielectric metasurface structure with a tilted subwavelength periodic perturbation. The proposed waveguide mode converter can be scaled to realize arbitrary waveguide mode conversion. As examples, two waveguide mode converters are experimentally demonstrated on a silicon‐on‐insulator wafer, which can convert the TE0 mode to the TE1 mode and the TE2 mode with coupling lengths of 5.75 and 6.736 µm, respectively. The conversion losses of <1 dB and crosstalk values of <−10 dB are achieved for both the TE0 ‐to‐TE1 and the TE0 ‐to‐TE2 mode converters. Abstract : A compact silicon waveguide mode converter is proposed and demonstrated using all‐dielectric metasurface structure with a tilted subwavelength periodic perturbation. As examples, two waveguide mode converters are experimentally demonstrated on a silicon‐on‐insulator wafer, which can convert the TE0 mode to the TE1 mode and the TE2 mode with coupling lengths of 5.75 and 6.736 µm, respectively.